Global asymmetries in international doctoral education - Elizabeth Agbor Eta; Nico Stockmann; Hanna Kontio; Elina Lehtomäki (Nordic Journal of Comparative and International Education)
Critical discourses of internationalisation of higher education and decoloniality have motivated this study unfolding global asymmetries present in Finnish doctoral education in the field of educational sciences. The data are doctoral dissertations related to education development in Africa completed at Finnish universities between 2000–2021 (N=100). We first describe the regional distribution and educational contexts where the research is located through a content analysis. Second, we conduct a network analysis of the institutional affiliations of co-authors of article-based dissertations, supervisors, and examiners of the doctoral dissertations and map the institutional connections in doctoral education. Then we present and discuss the findings from the content analysis, the dissertation mapping, and the institutional network analysis against the discourses of internationalisation and decoloniality that influence doctoral education in Finland and beyond. Finally, we reflect on implications for internationalisation of doctoral education in internationalised contexts, especially in North-South collaborations.